Capture and recover dissolved phosphorous from aqueous solutions by a designer biochar: Mechanism and performance insights. (July 2021) - Yang, Simin; Katuwal, Sarmila; Zheng, Wei; Sharma, Brajendra; Cooke, Richard
Abstract: Excessive phosphorus (P) in marine and freshwater systems has been identified as a primary perpetrator for the harmful and nuisance algal blooms. In this study, a novel designer biochar was produced from sawdust biomass treated with lime sludge prior to pyrolysis. The adsorption of dissolved P on the designer biochar was comprehensively evaluated under different experimental conditions. It revealed that the removal of dissolved P by the designer biochar was more efficient than unmodified biochar, lime sludge, and their post-combination, suggesting that the pretreatment of biomass with lime sludge for the designer biochar production has a significantly synergic effect on enhancing P removal. Post-adsorption characterization and mathematical modeling analyses indicated that the adsorption of dissolved P on the designer biochar could be controlled by multiple mechanisms including physical and chemical adsorption. The precipitation reaction between P anions and metal ions on the surface of the designer biochar was identified as a predominant mechanism. The X-ray diffraction showed that the precipitation reaction generated a series of P fertilizer forms depositing onto the designer biochar. In addition, batch adsorption experiments showed that both initial solution pH and coexisting anions had a lesser effect on the P removal by the designer biochar. This study proposed that the designer biochar could be a promising sorbent to remove dissolved P, and the nutrient-captured biochar could be used as a fertilizer to recover nutrients. Graphical abstract: Image 1 Highlights: A novel designer biochar is produced from the biomass pretreated with lime sludge. The designer biochar acts as an excellent sorbent for dissolved phosphorus removal. Adsorption processes and mechanisms of the designer biochar are appraised. The prospect of phosphorus-captured biochar as a fertilizer is highlighted.